Deciphering trait associated morpho-physiological responses in pearlmillet hybrids and inbred lines under salt stress - Kumar, Ashwani; Sheoran, Parvender; Mann, Anita; Yadav, Devvart; Kumar, Arvind; Devi, Sunita; Kumar, Naresh; Dhansu, Pooja; Sharma, Dinesh K. (Frontiers in Plant Science, 2023)
Pearl millet is a staple food for more than 90 million people residing in highly vulnerable hot arid and semi–arid regions of Africa and Asia. These regions are more prone to detrimental effects of soil salinity on crop performance in terms of reduced biomass and crop yields. We investigated the physiological mechanisms of salt tolerance to irrigation induced salinity stress (ECiw ~3, 6 & 9 dSm–1) and their confounding effects on plant growth and yield in pearl millet inbred lines and hybrids. On average, nearly 30% reduction in above ground plant biomass was observed at ECiw ~6 dSm-1 which stretched to 56% at ECiw ~9 dSm-1 in comparison to best available water. With increasing salinity stress, the crop performance of test hybrids was better in comparison to inbred lines; exhibiting relatively higher stomatal conductance (gS; 16%), accumulated lower proline (Pro; –12%) and shoot Na+/K+(–31%), synthesized more protein (SP; 2%) and sugars (TSS; 32%) compensating in lower biomass (AGB; –22%) and grain yield (GY: –14%) reductions at highest salinity stress of ECiw ~9 dSm–1. Physiological traits modeling underpinning plant salt tolerance and adaptation mechanism illustrated the key role of 7 traits (AGB, Pro, SS, gS, SPAD, Pn, and SP) in hybrids and 8 traits (AGB, Pro, PH, Na+, K+, Na+/K+, SPAD, and gS) in inbred lines towards anticipated grain yield variations in salinity stressed pearl millet. Most importantly, the AGB alone, explained >91% of yield variation among evaluated hybrids and inbreed lines at ECiw ~9 dSm–1. Cumulatively, the better morpho–physiological adaptation and lesser yield reduction with increasing salinity stress in pearl millet hybrids (HHB 146, HHB 272, and HHB 234) and inbred lines (H77/833–2–202, ICMA 94555 and ICMA 843–22) substantially complemented in increased plant salt tolerance and yield stability over a broad range of salinity stress. The information generated herein will help address in deciphering the trait associated physiological alterations to irrigation induced salt stress, and developing potential hybrids in pearl millet using these parents with special characteristics.